2016
DOI: 10.15252/embj.201592873
|View full text |Cite
|
Sign up to set email alerts
|

ER arrival sites for COPI vesicles localize to hotspots of membrane trafficking

Abstract: COPI-coated vesicles mediate retrograde membrane traffic from the cis-Golgi to the endoplasmic reticulum (ER) in all eukaryotic cells. However, it is still unknown whether COPI vesicles fuse everywhere or at specific sites with the ER membrane. Taking advantage of the circumstance that the vesicles still carry their coat when they arrive at the ER, we have visualized active ER arrival sites (ERAS) by monitoring contact between COPI coat components and the ER-resident Dsl tethering complex using bimolecular flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 105 publications
(146 reference statements)
0
22
0
Order By: Relevance
“…A prime candidate for this tethering activity is the evolutionarily conserved NRZ ( N BAS, R INT1, Z W10) protein tether. NRZ tether is a multi-subunit tether complex (MTC) that assembles at the surface of the ER ( Ren et al, 2009 ), is required for retrograde capture of membranes ( Aoki et al, 2009 ; Arasaki et al, 2006 ; Hirose et al, 2004 ), partially localises to ER exit sites ( Schröter et al, 2016 ) and interacts with SNAREs that we have shown previously are required for collagen export from the ER ( Nogueira et al, 2014 ; Santos et al, 2015 ). One component of the MTC (RINT1) was also identified in our screen for genes required for protein secretion ( Bard et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…A prime candidate for this tethering activity is the evolutionarily conserved NRZ ( N BAS, R INT1, Z W10) protein tether. NRZ tether is a multi-subunit tether complex (MTC) that assembles at the surface of the ER ( Ren et al, 2009 ), is required for retrograde capture of membranes ( Aoki et al, 2009 ; Arasaki et al, 2006 ; Hirose et al, 2004 ), partially localises to ER exit sites ( Schröter et al, 2016 ) and interacts with SNAREs that we have shown previously are required for collagen export from the ER ( Nogueira et al, 2014 ; Santos et al, 2015 ). One component of the MTC (RINT1) was also identified in our screen for genes required for protein secretion ( Bard et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is good evidence that RAB18 can bind the ER-resident Dsl1 protein complex (Gillingham et al, 2014), which tethers and fuses vesicles returning from the Golgi. This suggests that RAB18 may participate in the tethering of COPIcoated vesicles to the ER (Gillingham et al, 2014;Schroter et al, 2016). Interestingly, RAB18…”
Section: Role Of Golgi-associated Rab Proteins In the Brainmentioning
confidence: 98%
“…This COG-COPI interaction may then stimulate COG-SNARE and COG-SM interactions, which in turn promote SNARE formation and vesicle fusion. In support to these predictions, another tether, the ER-localized Dsl1 complex, can bind to COPI, suggesting functional significance for this conserved tether/coat interaction [13,[147][148][149]. Alternatively, the initial Rab-COG membrane association could change the conformation of flexible 'arms' of COG subunits, allowing them to establish interactions with CCTs, SNAREs, and SM proteins leading to productive vesicle tethering and fusion.…”
Section: What Is Primarily Responsible For Cog's Association With Memmentioning
confidence: 98%